Efektivitas Teratai (Nelumbo nucifera G.) dengan Berbagai Media Tanam untuk Fitoremediasi Air Asam Tambang - Raudhatunisya, Meuthea Najlaa; Mansur, Irdika; Hamim, Hamim (Pusat Penelitian Lingkungan Hidup, IPB (PPLH-IPB) dan Program Studi Pengelolaan Sumberdaya Alam dan Lingkungan, IPB (PS. PSL, SPs. IPB), 2025)
Acid mine drainage (AMD), characterized by high acidity and concentrations of heavy metals that can damage aquatic ecosystems, poses a serious environmental problem. This research aimed to analyze the effectiveness of Nelumbo nucifera Geartn. grown using a Floating Wetland System (FTW), treated with topsoil or bokashi, in altering pH and reducing heavy metals in coal mine AMD. The experiment was conducted for 14 days in a sedimentation pond of post-mining land at PT Bukit Asam, Palembang, Indonesia. Two FWS units were installed on the pond’s surface: one was enriched with topsoil, while the other was with bokashi. Fifteen N. nucifera plants were grown in each floating reactor, with plants grown directly in the AMD without the FWS used as the control group. Plantgrowth, media pH, and heavy metal contents were monitored during and after treatment. The results indicate that the system was capable of increasing the initial highly acidic AMD pH (pH 2.8) to a range close to neutral (6.5–6.9). The concentrations of Fe and Mn metals were significantly reduced through the absorption mechanism of roots, stems, and leaves, with an efficiency of more than 90%. XRD analysis also revealed the formation of secondary mineral phases that support vegetative growth in both reactors. These findings confirm that the FWS installed with the bokashi ameliorant and N. nucifera has great potential as a sustainable solution for acid mine drainage remediation.